PHYSICOCHEMICAL CHARACTERIZATION AND ANTIMICROBIAL PROPERTIES OF NAUCLEA LATIFOLIA (Smith) SEED OIL - Kabiru, H. D.; Yinusa, I.; Adam, D. S.; Abdulmalik, M. F. (FUDMA JOURNAL OF SCIENCES, 2023)
Nauclea latifolia (family: Rubiaceae) is a medicinal plant found in savannah region of tropical Africa and Asia. It is used traditionally in the management of various tropical diseases such as typhoid, malaria and hypertension. This study was carried out to characterize oil extracted from the seed of Nauclea latifolia. Physicochemical properties, antimicrobial activities and fatty acids composition of the oil sample were determined using standard procedures. The seeds were removed from ripe fruits of N. latifolia, ground into powder and extracted using Soxhlet apparatus at 67 °C for 2 h using n-hexane as the solvent. The oil yield was 11.10%. The oil was liquid at room temperature, had a fruity smell and pale yellow colour. pH and specific gravity of the oil were 5.02 and 0.975g/cm3 respectively. Physicochemical parameters of the oil: acid value, iodine value, peroxide value and saponification value were 4.21mg/KOH/kg, 2.538mg/kg, 12.40 mEqO2/kg and 23.6425mg/KOH/kg respectively. The oil showed moderate zone of inhibition against Streptococcus pyogene (16mm) and Staphylococcus aureus(13mm) and a low zone of inhibition against Pseudomonas aeruginosa (9mm) and   Proteus spp (11mm). The predominant fatty acids present in the oil were Palmitic acid (20.47%), Stearic acid (4.57%) oleic acids (23.46%), Linoleic acid (10.52%),  Behenic acid (12.74%) and Erucic acid(1.60%).  The ratio of saturated to unsaturated fatty acids was 0.8.  The oil of N. latifolia showed moderate physicochemical and fatty acid properties. The study also revealed the potential of the oil in the treatment of infections caused by some of the tested microbes